(untitled) (Journal of Telenursing (JOTING), 2023)
This research aims to determine the socio-cultural picture of early marriage in the Selayar Islands district. This research method uses a qualitative method with a phenomenological approach, namely collecting data by conducting in-depth interviews with 16 informants aged 15-18 years who have experienced early marriage. The results of the research show that there are several things that are the main causes of early marriage in the Selayar Islands district, precisely in Benteng sub-district, South Selawesi, namely; arranged marriages, social environment, economics and promiscuity. Perceptions about children marrying at an early age, some respondents said the reason for marrying at an early age was because of the arranged marriage element, the element of like-mindedness and the element of necessity due to promiscuity. Perceptions about children getting married at an early age, some respondents said that their parents did not agree with their marriage. In conclusion, there are several things that are the main causes of early marriage in the Selayar Islands Regency, namely: arranged marriages, social environment and promiscuity. Keywords: Early Marriage, Image, Socio-Cultural.